Waduk Purboyo Sebagai Wahana Wisata Didukung Dengan Budidaya Dan Produk Olahan Ikan - Nurin Fitriana; Eny Dyah Yuniwati; Rizalnur Firdaus; Azhar Adi Darmawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Purwosekar Village, Tajinan District, Malang Regency is the location of community service activities that aim to 1) Create a tourist area around the Purboyo reservoir; 2 Create a fish pond area around the reservoir flow and its processed products as potential villages; 3). Creating an entertainment area in the reservoir area and its surroundings. The method used in service activities in Purwosekar Village, Tajinan District, Malang Regency is carried out with several activities, namely maintaining clean reservoir conditions, training related to the development of processed products that support local potential. In this case, training activities for fish cultivation and processed fish products were carried out in the pond area around the Purboyo reservoir. This service activity has an output target in the form of creating a tourist area in the reservoir area by empowering the potential of the reservoir area, namely ponds for fish cultivation and processed products. Thus, it is hoped that in the end it will be able to develop the reservoir area into a tourism vehicle to help spread the promotion of products made by rural communities and improve the economy in Purwosekar Village.